Levonorgestrel-releasing intrauterine device treatment in heavy menstrual bleeding: Correlation with endometrial pathology and quality of life - Selma Atiye Kolcu; Ebru Kara; Elif Yıldız; Arzu Çetin (PLoS ONE, 2025)
The aim of the study was to compare the effects of 52 mg Levonorgestrel-releasing intrauterine device (LNG-IUD), which is frequently used in patients with heavy menstrual bleeding, on quality of life according to benign endometrial pathology patterns. The study was designed retrospectively.143 patients between the ages of 28 and 54, who underwent endometrial sampling due to heavy menstrual bleeding and then the 52 mg LNG-IUD was placed, were included in the study. The most commonly observed results in endometrial pathology were divided into 2 groups: normal cycle patterns and hormonal imbalance patterns. Change in quality of life after LNG-IUD insertion was assessed using the Menorrhagia Multiattribute Scale (MMAS), the 36-Item Short Form Health Survey (SF-36), and the Beck Depression Inventory. In both groups, a significant increase was observed in all parameters of the SF-36 quality of life scale and the MMAS total score after LNG-IUD use compared to the pre-IUD period (p < 0.05) (MMAS increased from 51.9 ± 27.8% to 83.8 ± 26.2% at 6 months), and a significant decrease was observed in the Beck Depression Inventory score and depression rate (p < 0.05). However, there was no significant difference in the changes in quality of life questionnaires before and after LNG-IUD use between the groups (p > 0.05). The LNG-IUD provides substantial improvements in bleeding control and quality of life among women with heavy menstrual bleeding, and these effects are not influenced by endometrial pathology results.